Photo-molecular high temperature superconductivity - Buzzi, M; Nicoletti, D; Fechner, M; Tancogne-Dejean, N; Sentef, MA; Georges, A; Biesner, T; Uykur, E; Dressel, M; Henderson, A; Siegrist, T; Schlueter, JA; et al. (American Physical Society, 2020)
The properties of organic conductors are often tuned by the application of chemical or external pressure, which change orbital overlaps and electronic bandwidths while leaving the molecular building blocks virtually unperturbed. Here, we show that, unlike any other method, light can be used to manipulate the local electronic properties at the molecular sites, giving rise to new emergent properties. Targeted molecular excitations in the charge-transfer salt κ−(BEDT−TTF)2 Cu[N(CN)2] Br induce a colossal increase in carrier mobility and the opening of a superconducting optical gap. Both features track the density of quasiparticles of the equilibrium metal and can be observed up to a characteristic coherence temperature T∗≃50K, far higher than the equilibrium transition temperature TC=12.5K. Notably, the large optical gap achieved by photoexcitation is not observed in the equilibrium superconductor, pointing to a light-induced state that is different from that obtained by cooling. First-principles calculations and model Hamiltonian dynamics predict a transient state with long-range pairing correlations, providing a possible physical scenario for photomolecular superconductivity.